Diversity of Cladocera of the Shatt Al-Arab River, Southern Iraq - Ajeel , S.G.; Abbas, M.F. (Mesopotamian Journal of Marine Sciences, 2022)
Samples of zooplankton were collected monthly from three stations in the Shatt Al-Arab region (Al-Hartha, Garmat Ali and Al-Ashaar) for the period from June 1996 to May 1997 using a plankton net with a mesh-size of 120 µm. Twenty species of Cladocera belonging to 14 genera were recorded in the study area. The total number of Cladocera ranged between 0.3 ind./m3 during October 1996 and 7207 ind./m3 during April 1997. The highest values of Shannon Weaver diversity index and Richness index were recorded at station 3 during December and June (1.8 and 7.62, respectively), and the lowest values were (0) and 0.23, reported in July at station 3 and in March at station 2. The highest value of Evenness (1.0) was recorded at station 3, during October and the lowest (0.01) was recorded at station 2 during April. The Jaccard index indicates that the highest similarity was between stations 1 and 3 (34.48) and the lowest was between stations 2 and 3 (30.49).